2012
DOI: 10.1158/1078-0432.ccr-11-3165
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Pharmacokinetic and Pharmacodynamic Study of CHR-3996, an Oral Class I Selective Histone Deacetylase Inhibitor in Refractory Solid Tumors

Abstract: Purpose: This clinical trial investigated the safety, tolerability, pharmacokinetic (PK), and pharmacodynamic (PD) profile of CHR-3996, a selective class I histone deacetylase inhibitor.Patients and Methods: CHR-3996 was administered orally once a day. This phase I trial used a 3þ3 doseescalation design. PK profiles were analyzed by liquid chromatography-tandem mass spectroscopic methods and PD studies were conducted using ELISA studying histone H3 acetylation in peripheral blood mononuclear cells.Results: Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…Rash was the most frequent adverse event and DLT; two distinct appearances were noted: a reversible maculopapular rash associated with pruritus consistent with our previous experience with MK-2206 (17); and an erythematous acneiform rash associated with selumetinib that improved with topical steroids or oral tetracycline therapy (24). Other DLT included diarrhoea and stomatitis, which appeared to be dose-related.…”
Section: Resultssupporting
confidence: 76%
“…Rash was the most frequent adverse event and DLT; two distinct appearances were noted: a reversible maculopapular rash associated with pruritus consistent with our previous experience with MK-2206 (17); and an erythematous acneiform rash associated with selumetinib that improved with topical steroids or oral tetracycline therapy (24). Other DLT included diarrhoea and stomatitis, which appeared to be dose-related.…”
Section: Resultssupporting
confidence: 76%
“…Among 14 evaluable phase I patients, 2 out of 5 patients with PDAC showed partial response with tumour shrinking and 1 patient had stable disease (American Society of Clinical Oncology Meeting 2008, abstract 4625). In contrast to these results that suggest synergism of the gemcitabine/HDACi combination in patients with PDAC,39 the majority of studies revealed restricted effects in a limited number of patients with distinct histological PDAC subgroups40 41 or even characterised combination with HDACi to be inferior to gemcitabine monotherapy in this tumour entity (NCT00004861) 42…”
Section: Translational Approaches To Tackle Epigenetic Dysregulation mentioning
confidence: 99%
“…In estrogen receptor-positive breast cancer, the combination of exemestane with entinostat improves median PFS to 4.3 months and median OS to 28.1 months, whereas median PFS and OS is 2.3 and 19.8 months, respectively, in the exemestane plus placebo group (139). Other HDAC inhibitors, such as ITF2357, CHR-3996, and JNJ-26481585, have been studied and show promising antitumor effect (140)(141)(142).…”
Section: Hdac Inhibitorsmentioning
confidence: 99%